Analysis of Law Enforcement Against Children as Perpetrators of Violent Theft: A Case Study of the Southeast Aceh Police - Irvandi, Irvandi; Ramadhan, M. Citra; Frensh, Wenggedes (Journal of Public Representative and Society Provision, 2025)
Law enforcement against children as perpetrators of violent theft is a complex issue that requires special attention, especially in the application of the principle of restorative justice in accordance with Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (SPPA). This study aims to analyze the applicable legal rules, the implementation of law enforcement by the Southeast Aceh Police, as well as the obstacles faced in handling cases of children as perpetrators of violent theft. The research method used is qualitative with a case study approach, which involves in-depth interviews, observations, and document studies. The results of the study show that the rule of law prioritizes the principles of child rehabilitation and protection through a diversion mechanism to prevent children from the formal criminal justice system. The Southeast Aceh Police has tried to apply this principle, despite facing various obstacles, such as limited facilities for children, lack of trained human resources, and low public understanding of the restorative approach. This research emphasizes the importance of a holistic approach that involves various parties to increase the effectiveness of law enforcement against children. Support in the form of training officials, improving child-friendly facilities, and community education is needed to ensure the success of a fair juvenile criminal justice system and support the social reintegration of child offenders. Thus, this system can function optimally to protect children's rights, create justice for victims, and restore social harmony.